Introduction of team‐based learning improves understanding of glucose metabolism in biochemistry among undergraduate students. Issue 3 (30th December 2020) - Eguchi, Hironobu; Sakiyama, Haruhiko; Naruse, Hitoshi; Yoshihara, Daisaku; Fujiwara, Noriko; Suzuki, Keiichiro
Abstract: Team‐based learning (TBL) is an active learning method used in many educational institutions. However, there are few examples of its use in basic medicine, such as biochemistry in medical schools. This study used TBL to teach glucose metabolism to first‐year medical students. The process was in four phases: preclass preparation, readiness assurance tests, advanced questions, and a TBL test, with peer evaluation and a questionnaire. There were positive correlations between the TBL test, peer evaluation, and individual readiness test performance. Tests were taken immediately after learning and 2 weeks later, and scores decreased significantly less with TBL than traditional lectures (−2.3% vs. −17.5%). This suggests that TBL was more effective than traditional lectures in supporting knowledge retention. We used a Moodle system to facilitate communication between students and teachers, and this was evaluated positively by both groups. It was particularly useful for managing TBL. These findings suggest that TBL could be used to improve student performance in biochemistry.